Blood-Cerebrospinal Fluid Barrier Gradients in Mild Cognitive Impairment and Alzheimer's Disease: Relationship to Inflammatory Cytokines and Chemokines - Ott, Brian R.; Jones, Richard N.; Daiello, Lori A.; de la Monte, Suzanne M.; Stopa, Edward G.; Johanson, Conrad E.; Denby, Charles; Grammas, Paula (Frontiers in Aging Neuroscience, 2018)
Background: The pathophysiology underlying altered blood-cerobrospinal fluid barrier (BCSFB) function in Alzheimer’s disease (AD) is unknown but may relate to endothelial cell activation and cytokine mediated inflammation. Methods: Cerebrospinal fluid (CSF) and peripheral blood were concurrently collected from cognitively healthy controls (N=21) and patients with mild cognitive impairment (MCI) (N=8) or AD (N=11). The paired serum and CSF samples were assayed for a panel of cytokines, chemokines, and related trophic factors using multiplex ELISAs. Dominance analysis models were conducted to determine the relative importance of the inflammatory factors in relationship to BCSFB permeability, as measured by CSF/serum ratios for urea, creatinine, and albumin. Results: BCSFB disruption to urea, a small molecule distributed by passive diffusion, had a full model coefficient of determination (r2) =.35, and large standardized dominance weights (>.1) for monocyte chemoattractant protein-1, interleukin (IL)-15, IL-1rα, and IL-2 in serum. BCSFB disruption to creatinine, a larger molecule governed by active transport, had a full model r2=.78, and large standardized dominance weights for monocyte inhibitor protein-1b in CSF and tumor necrosis factor-α in serum. BCSFB disruption to albumin, a much larger molecule, had a full model r2=.62, and large standardized dominance weights for IL-17a, interferon-gamma, IL-2, and VEGF in CSF, as well IL-4 in serum. Conclusions: Inflammatory proteins have been widely documented in the AD brain. The results of the current study suggest that changes in BCSFB function resulting in altered permeability and transport are related to expression of specific inflammatory proteins, and that the shifting distribution of these proteins from serum to CSF in AD and MCI is correlated with more severe perturbations in BCSFB function.